DEVELOPMENT OF PROFESSIONAL TEACHER KNOWLEDGE WITHIN COLLABORATIVE PRACTICES: A STUDY IN THE CONTEXT OF TEACHER INITIAL EDUCATION - Ferreira, Janaína da Silva; Neto, Samuel de Souza [UNESP]; Batista, Paula Maria Fazendeiro (My University, 2022)
This study analyzed the construction of teaching professional knowledge of Physical Education residents in the context of the Pedagogical Residency program within a community. One supervisor, three collaborating teachers and 24 residents (undergraduate students) participated. They met weekly for 18 months in a dynamic of constructive-collaborative work. Data sources were reports, teaching cases, and reflective portfolios produced by six purposefully selected residents. Data were triangulated and subjected to thematic analysis. Residents developed different knowledge, but the skills related to professional action stood out the most. The formative devices contributed to developing the residents’ reflective, critical, and communicative rationality. The community proved to be a space for sharing, for the development of close and horizontal interactions between different types of knowledge and professionals, allowing the transition from knowledge-to-practice and knowledge-in-practice to knowledge-of-practice, as well as the transition from a peripheral and individual position of knowledge for a knowledge built collectively.
DESARROLLO DEL CONOCIMIENTO PROFESIONAL DOCENTE EN EL SENO DE LAS PRÁCTICAS COLABORATIVAS: UN ESTUDIO EN EL CONTEXTO DEL PROGRAMA DE FORMACIÓN DE PROFESORADO
DESENVOLVIMENTO DO CONHECIMENTO PROFISSIONAL DOCENTE NO SEIO DE PRÁTICAS COLABORATIVAS: UM ESTUDO NO CONTEXTO DE UM PROGRAMA DE FORMAÇÃO DE PROFESSORES
Keywords: Collaborative learning; Knowledge bases; Learning Community; Teacher Education